The Alchemist: Figurative Language Translation Analysis - Sastrawinata, Chairunisa Sonya (Universitas Brawijaya, 2023)
This study investigates the translation methods and analysis of figurative language in the novel â€œThe Alchemistâ€ by Paulo Coelho from English to Indonesian. The main theory used to help find the answer in the process is Peter Newmark and Chestermanâ€™s theory, along with other supporting journals. The research method applied is qualitative descriptive. The result showed the writer found 54 syntactic strategy (47 literal translation, 1 calque, 2 phrase structure change, 1 cohesion change, 2 sentence structure change, 1 transposition), 10 semantic strategy (10 synonymy ), and 7 pragmatic strategy (7 explicitness change).